1957
DOI: 10.1017/s0021859600031762
|View full text |Cite
|
Sign up to set email alerts
|

The apparent digestibility of crude protein by the ruminant: II. The general equation and some of its implications

Abstract: The general equation, y = 70 log x − 15, connecting y, the digestibility coefficient, to x, the percentage of crude protein in the dry matter of the feed of ruminants, which was proposed in an earlier paper, has been shown to fit all the directly determined world data for cattle, sheep and goats which have been published by Schneider (1947). It is applicable to rations composed of both single and mixed feeds for it is the total percentage of crude protein in the ration which determines its digestibility.The eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Assurance levels (per kilogram of product): calcium, 200.00 g; phosphorus, 60.00 g; magnesium, 20.00 g; sulfur, 20.00 g; sodium, 70.00 g; potassium, 35.00 g; copper, 700.00 mg; iodine, 40.00 mg; cobalt, 15.00 mg; iron, 700.00 mg; manganese, 1600.00 mg; zinc, 2500.00 mg; selenium, 19.00 mg; chromium, 10.00 mg; fluorine (max), 600.00 mg; vitamin A, 200 000.00 international units (IU); vitamin E, 1500.00 IU; vitamin D3, 50 000.00 IU. The DM and nutrient digestibility coefficients were calculated according to the equation by French et al (1957): digestibility coefficient 0(kg nutrient intake(kg nutrient excreted)= (kg nutrient intake))100:…”
Section: Methodsmentioning
confidence: 99%
“…Assurance levels (per kilogram of product): calcium, 200.00 g; phosphorus, 60.00 g; magnesium, 20.00 g; sulfur, 20.00 g; sodium, 70.00 g; potassium, 35.00 g; copper, 700.00 mg; iodine, 40.00 mg; cobalt, 15.00 mg; iron, 700.00 mg; manganese, 1600.00 mg; zinc, 2500.00 mg; selenium, 19.00 mg; chromium, 10.00 mg; fluorine (max), 600.00 mg; vitamin A, 200 000.00 international units (IU); vitamin E, 1500.00 IU; vitamin D3, 50 000.00 IU. The DM and nutrient digestibility coefficients were calculated according to the equation by French et al (1957): digestibility coefficient 0(kg nutrient intake(kg nutrient excreted)= (kg nutrient intake))100:…”
Section: Methodsmentioning
confidence: 99%
“…As a result, by the end of the dry season, a random sample of animals of all ages and sexes showed that their diet contained only 2.18% crude protein. French, Glover & Duthie (1957) and Glover & Duthie (1958) have shown that the digestibility of crude protein is remarkably similar for ruminants in general and even for non-ruminants. Furthermore, from digestibility trials, P. Arman (personal communication) found that buffalo were very similar to cattle.…”
Section: The Qualit! Of Food In the Serengetimentioning
confidence: 99%
“…Bredon,Harker & Marshall (1 963) found that the degree of digestibility of dry grass-the digestibility coefficient (DC)-was related to the % crude protein (CP) in the diet of cattle by DC = 100.89 log CP -44.45 and this gives zero digestibility at 2.76% crude protein. But protein and energy assimilation remain low even above this level due to the inhibition of the rumen micro-organisms untiI a higher quality at intake is attained: the minimum level of crude protein for maintenance in tropical cattle has been estimated to lie between 4% and 8% with most measurements approaching 5% (French, 1957;Plowes, 1957;French et al, 1957;Bredon & Wilson, 1963;Agricultural Research Council, 1965;Milford & Minson, 1966). The value of 5% crude protein has been used in Fig. I to indicate the minimum maintenance level.…”
Section: The Qualit! Of Food In the Serengetimentioning
confidence: 99%
See 1 more Smart Citation